Variation in activation marker expression within the platelet population – a new parameter for evaluation of platelet flow cytometry data. (17th November 2022) - Tynngård, Nahreen; Alshamari, Aseel; Månsson, Freja; Ramström, Sofia
Abstract: In flow cytometry, individual cells are investigated. Platelet activation is normally reported in form of percentage of platelets expressing the marker (positive platelets) and/or mean/median fluorescence intensity (MFI) for the entire analyzed population. None of these take into account the variance of the marker expression between individual platelets. This can be obtained as data on coefficient of variation (CV). This study explores if CV provides additional information regarding platelet function. Samples from platelet concentrates (PCs) prepared by apheresis- (n = 13) and interim platelet unit (IPU) technique (n = 26) and stored for 6–7 days were included and compared. Spontaneous- and agonist-induced expression of activation markers (fibrinogen binding and exposure of P-selectin, LAMP-1, and CD63) was investigated as percentage positive platelets, MFI and CV. Spontaneous expression of P-selectin as percentage positive platelets and MFI was higher for IPU PCs than apheresis PCs, which in contrast had higher agonist-induced activation. CV for spontaneous fibrinogen binding and P-selectin exposure was larger for apheresis PCs, while IPU PCs generally had larger CV for P-selectin, LAMP-1, and CD63 after agonist stimulation. Our findings show that CV adds additional information when assessing platelet activation by providing data on the variation in activation responses within the platelet population.